Analysis of Maximum Weaving Length and Lane-Changing Rate for Two-Sided Weaving Section for Federal Road FT050 Based on HCM 2010 - Prasetijo, Joewono; Baba, Ishak; Muthukrisnan, Narain s/o; Atasha Arifin, Nurul Elena; David Daniel, Basil; Sanik, Mohd Erwan (International Journal of Integrated Engineering, 2018)
Weaving is defined as a movement of vehicles that crossing over the direct traffic from on-ramp to off-ramp. Apparently, weaving maneuver lead to collision risk and weaving turbulence especially at two-sided weaving section. In order to analyze the operational of two-sided weaving segment on Federal Route 50 (FT050), the following study recognize the maximum weaving length and lane-changing rate. Video recording technique was used at two different locations that are Site A (KM15) and Site B (KM16). The volume data was extracted by playback the video using computer. Analysis was made using Microsoft Excel spreadsheet and applied the methodology in the Highway Capacity Manual 2010. The study found that Site A has more tendencies to encounter longer weaving turbulence with maximum weaving length ranging from (1952 m – 2120 m) compared to site B that is 1866 m - 1882 m. Site A with a longer distance of weaving section 358 m has higher intense of total lane-changing rate that is 1142 lc/h compared to Site B with a distance of weaving section 316 m has total lane-changing rate of 812 lc/h. Shorter weaving distance cause less lane-changing activity because drivers does not prefer to perform weaving at shorter weaving section as it is forced the drivers to perform weaving drastically in more crammed situation and risk to dealing with accident is huge. The findings shall help to understand more about causes of weaving turbulence at weaving section by using HCM 2010